Chronic pyrrolizidine alkaloid toxicosis in a heifer - Barraza, Vanessa; Flores, Mariana Martins (Brazilian Journal of Veterinary Pathology, 2021)
This heifer came from a group of cattle with chronic diarrhea and emaciation. Some of the animals also had neurological signs, predominantly aggressiveness. Two animals had already died spontaneously after worsening of the clinical signs. The farmer had kept these animals on native pasture during the winter, and he reported that the vegetation had been scarce in that period. On clinical exam, the animals were in bad body condition, with some presenting dyspnea, subcutaneous edema mainly affecting the dewlap, and abdominal distention.